Development of the small scale industeries in Bihar : case study of Bihar state small scale industries corporation - "Akram, S." (Delhi, 1984)
The growth of small-scale industries in our country during the last 30 years is rightly regarded as on eof the most significant features of planned economic development. The very concept of small scale industry, as we now know it, was not in vogue on the eve of Independence. Rural and cottage industries which constituted the indigenous sector of our industries were widespread throughout the length and breadth of the country.
Keywords: Small scale industeries